Avaliação do uso de uma estrutura de nylon modificada como reforço de prótese totalmente acrílica implantossuportada - Gonçalves, Fernanda de Cássia Papaiz [UNESP] (2015)
The study evaluated the behavior of a new compound of experimental nylon fiber, with the purpose of increasing the mechanical strength of the material and improving the strain distribution to the fullest extent of the prosthesis to the long axis of the implants reducing the risk of fractures and faults in the system and therefore increasing longevity. For this considered protocol type prostheses without metal bar, with and without incorporating reinforcement (nylon), varying the extent of the region of the cantilever to the first molar / second premolar (n = 6). The samples were subjected to analysis by extensometer strain (extensometria ) and load of 30 kg, and the maximum load test to fracture the EMIC (1000 kgf, 2 mm / min). It can be concluded that the incorporation of reinforcing mesh increased maximum load values regardless of the extent of the cantilever, and exhibit lower values microstrain around all implants. The cantilever extensions in premolar (5 mm) in addition of having the smallest microstrain values compared the extent to molar (15mm) also showed the highest maximum load values to fracture